2019
DOI: 10.1002/adhm.201900622
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Doped PEDOT for Enhanced Electrode Coatings and Drug Delivery

Abstract: In order to address material limitations of biologically interfacing electrodes, modified silica nanoparticles are utilized as dopants for conducting polymers. Silica precursors are selected to form a thiol modified particle (TNP), following which the particles are oxidized to sulfonate modified nanoparticles (SNPs). The selective inclusion of hexadecyl trimethylammonium bromide allows for synthesis of both porous and nonporous SNPs. Nonporous nanoparticle doped polyethylenedioxythiophene (PEDOT) films possess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 60 publications
1
85
0
Order By: Relevance
“…[ 93 ] In 2018, they further extended the targeted drug to Levodopa, i.e., a treatment for Parkinson's disease. [ 94 ] Specifically, gold nanodendrites with large surface areas were synthesized via an overpotential deposition approach on the evaporated Au/Cr conductive layer, offering adequate interfaces for enzyme loading and molecular sensing. The performance of prolonged, continuous, and noninvasive drug monitoring in human subjects enabled dosage optimization in a point‐of‐care and precise manner.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 93 ] In 2018, they further extended the targeted drug to Levodopa, i.e., a treatment for Parkinson's disease. [ 94 ] Specifically, gold nanodendrites with large surface areas were synthesized via an overpotential deposition approach on the evaporated Au/Cr conductive layer, offering adequate interfaces for enzyme loading and molecular sensing. The performance of prolonged, continuous, and noninvasive drug monitoring in human subjects enabled dosage optimization in a point‐of‐care and precise manner.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…[ 100 ] Woeppel et al precisely controlled the drug release from the sulfonated silica NP‐doped composite by electrochemical method ( Figure 6 A). [ 94 ] In this article, SiO 2 NP dopants not only provided a potential drug delivery library but also maintained favorable electrochemical properties. Controlled release of DOX within a few seconds were achieved by the electron injection into doxorubicin (DOX)@nanographene oxide/platinum micromachines, with the reduced nanographene oxide serving as a drug‐loading platform.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…inflammation and scar tissue formation around the metal–tissue interface) that motivates the development of softer non‐degradable conductive coatings (e.g. conductive polymers), 32–39 potentially using microscale/nanoscale patterns to instruct cell behaviour, 40,41 or indeed capable of delivering bioactive substances from the electrode coating (e.g. anti‐inflammatories such as dexamethasone phosphate (DMP) and antimicrobials) 42 …”
Section: Introductionmentioning
confidence: 99%
“…In this study, 0.5 μg/cm 2 dexamethasone can be released after each CV cycle and up to a total of nearly 16 μg/cm 2 can be released after 30 CV cycles ( Figure 1(d)). To further enhance the drug release performance and drug-loading capacity of the ICPs, Woeppel et al reported the usage of functionalized negatively charged porous silica nanoparticles as the dopant for PEDOT [46]. The silica nanoparticle-doped PEDOT showed significantly enhanced doxorubicin (DOX) release profiles (up to 7-folds higher than the control) by applying electrical stimulations; different kinds of drugs, e.g., fluorescein and DNQX, have been loaded into the porous silica nanoparticle-doped PEDOT and demonstrated controllable release profiles in vivo.…”
Section: Introductionmentioning
confidence: 99%